Enhancing Academic Integrity Amidst AI Challenges in Higher Education - Kouider , MAKHLOUF (Journal of Science and Knowledge Horizons, 2025)
The integration of artificial intelligence (for short, AI) in higher education institutions has raised significant concerns about maintaining academic integrity. This paper thoroughly analyses the evolving dynamics of academic integrity in the new era of AI, addressing both the challenges and ethical implications of AI technologies. It highlights the importance of robust policies, educational initiatives, and collaborative efforts among stakeholders to enhance a culture of integrity within academic communities. The findings emphasize the necessity for a balanced approach that harnesses the power of AI while safeguarding core principles of academic integrity. By contributing to the ongoing discourse on AI in education, this research offers practical recommendations for higher education institutions navigating this complex issue